ANIMASI KARTUN SEBAGAI MEDIA PEMBELAJARAN IPAS YANG EFEKTIF DI JENJANG SEKOLAH DASAR - Zulfa Rosita Anggraini; Evi Rizqi Salamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology demands more innovative learning approaches in elementary schools. One potential medium that can be utilized is cartoon animation. This study aims to describe the effectiveness of cartoon animation in improving students’ focus and understanding in IPAS learning. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that cartoon animation creates an engaging and interactive learning environment. This medium helps students grasp abstract concepts in a more concrete way and enhances their participation and learning motivation. The visual and simplified presentation of the material allows students to understand concepts more quickly, while also supporting teachers in explaining abstract content. Compared to conventional methods, this medium offers a more enjoyable and interactive learning experience and assists teachers in delivering complex material more clearly. In conclusion, cartoon animation is proven to be an effective medium for teaching IPAS, as it provides contextual, interactive learning aligned with the principles of the Merdeka Curriculum.